(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Attempts to identify factors capable of inducing Brachymeria intermedia to oviposit in an artificial host are reported. The development of an artificial substrate for in vitro egg laying of this hymenopterous parasitoid is also described. When presented with a choice between pupae of the factitious host Galleria mellonella and a blank cell in a Y tube olfactometer the females did not show a significant olfactory preference for the pupae. The response of B. intermedia females to G. mellonella pupae washed in hexane or untreated was also not significantly different. The role of kairomonal cues in the cuticle of G. mellonella pupae in attracting B. intermedia females was therefore not clear. Cylindrical host shape, on the other hand, was apparently important in inducing parasitoid oviposition. In fact, the females were observed to probe cylinder-shaped artificial substrates with their ovipositors even in the absence of chemical cue. When cylinder-shaped and purposefully flattened G. mellonella cuticles were exposed to parasitoid females oviposition holes were recorded only in the former and none in the latter. Cylinder-shaped artificial hosts composed of an agar-water suspension and G. mellonella haemolymph encapsulated in Parafilm were hence prepared and exposed to B. intermedia females. Some eggs were recorded in artificial pupae containing 50% or 25% haemolymph. No eggs were found in ’the pupae containing agar-water suspension alone, or 75% or 100% haemolymph. These results suggest that G. mellonella haemolymph contains ovipositional kairomones, an excess of which, however, prevents B. intermedia females from ovipositing.